Combination of Intra-Articular and Intraosseous Injections of Platelet Rich Plasma for Severe Knee Osteoarthritis: A Pilot Study. (4th July 2016) - Sánchez, Mikel; Delgado, Diego; Sánchez, Pello; Muiños-López, Emma; Paiva, Bruno; Granero-Moltó, Froilán; Prósper, Felipe; Pompei, Orlando; Pérez, Juan Carlos; Azofra, Juan; Padilla, Sabino; Fiz, Nicolás
Abstract : The aim of this study was to assess a novel approach to treating severe knee osteoarthritis by targeting synovial membrane, superficial articular cartilage, synovial fluid, and subchondral bone by combining intra-articular injections and intraosseous infiltrations of platelet rich plasma. We explored a new strategy consisting of intraosseous infiltrations of platelet rich plasma into the subchondral bone in combination with the conventional intra-articular injection in order to tackle several knee joint tissues simultaneously. We assessed the clinical outcomes through osteoarthritis outcome score (KOOS) and the inflammatory response by quantifying mesenchymal stem cells in synovial fluid. There was a significant pain reduction in the KOOS from baseline ( 61.55 ± 14.11 ) to week 24 ( 74.60 ± 19.19 ), after treatment ( p = 0.008 ), in the secondary outcomes (symptoms, p = 0.004 ; ADL, p = 0.022 ; sport/rec., p = 0.017 ; QOL, p = 0.012 ), as well as VAS score (p < 0.001 ) and Lequesne Index ( p = 0.008 ) . The presence of mesenchymal stem cells in synovial fluid and colony-forming cells one week after treatment decreased substantially from 7.98 ± 8.21 MSC/ μ L to 4.04 ± 5.36 MSC/ μ L ( p = 0.019 ) and from 601.75 ± 312.30 to 139.19 ± 123.61 ( p = 0.012 ), respectively. Intra-articular injections combined with intraosseous infiltrations of platelet rich plasma reduce pain and mesenchymal stem cells in synovial fluid, besides significantly improving knee joint function in patients with severe knee osteoarthritis. This trial is registered on EudraCT with the number 2013-003982-32 .